Employee Loyalty Transformation: Motivation, Discipline, Work Environment, Commitment as a Moderator - Wijayanti, Tri Cicik (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study investigates the impact of work motivation, work discipline, and work environment on employee loyalty at PT Java Indosinergi Creative, with commitment serving as a mediating variable. Data were collected through surveys from the company's permanent employees and analyzed using robust statistical methods. The findings reveal several significant insights: firstly, work motivation positively influences employee loyalty, indicating that motivated employees demonstrate stronger allegiance to the organization. Secondly, work discipline also plays a crucial role, as employees with higher discipline levels exhibit greater loyalty. Interestingly, while a conducive work environment shows a positive influence on loyalty, its direct impact is not statistically significant, suggesting the presence of other influential factors. Moreover, employee commitment was identified as a mediator between work motivation/discipline and employee loyalty, underscoring the pivotal role of commitment in enhancing employee allegiance. However, commitment does not significantly mediate the relationship between the work environment and employee loyalty. These results are consistent with previous research but emphasize the necessity for further exploration into additional factors influencing employee loyalty. Practically, organizations are advised to bolster employee motivation and discipline while fostering a supportive work environment to bolster loyalty effectively. Socially, this research aids companies in comprehending the nuances of employee loyalty dynamics, enabling them to craft more effective human resource management strategies that promote retention and cultivate a harmonious workplace culture.